Influence of uremia and hemodialysis on the turnover and metabolic effects of glucagon. - Sherwin, R S (1976)
To evaluate the mechanism and role of hyperglucagonemia in the carbohydrate intolerance of uremia, 19 patients with chronic renal failure (12 of whom had undergone chronic hemodialysis for at least 11 mo) and 35 healthy control subjects were studied. Plasma glucagon, glucose, and insulin were measured in the basal state, after glucose ingestion (100 g), after intravenous alanine (0.15 g/kg), and during a 3-h continuous infusion of glucagon (3 ng/kg per min) which in normal subjects, raised plasma glucagon levels into the upper physiological range. Basal concentrations of plasma glucagon, the increment in glucagon after infusion of alanine, and post-glucose glucagon levels were three- to fourfold greater in uremic patients than in controls. The plasma glucagon increments after the infusion of exogenous glucagon were also two- to threefold greater in the uremics. The metabolic clearance rate (MCR) of glucagon in uremics was reduced by 58% as compared to controls. In contrast, the basal systemic delivery rate (BSDR) of glucagon in uremics was not significantly different from controls. Comparison of dialyzed and undialyzed uremics showed no differences with respect to plasma concentrations, MCR, or BSDR of glucagon. However, during the infusion of glucagon, the increments in plasma glucose in undialyzed uremics were three- to fourfold greater than in dialyzed uremics or controls. When the glucagon infusion rate was increased in controls to 6 ng/kg per min to produce increments in plasma glucagon comparable to uremics, the glycemic response remained approximately twofold greater in the undialyzed uremics. The plasma glucose response to glucagon in the uremics showed a direct linear correlation with oral glucose tolerance which was also improved with dialysis. The glucagon infusion resulted in 24% reduction in plasma alanine in uremics but had no effect on alanine levels in controls. It is concluded that (a) hyperglucagonemia in uremia is primarily a result of decreased catabolism rather than hypersecretion of this hormone; (b) sensitivity to the hyperglycemic effect of physiological increments in glucagon is increased in undialyzed uremic patients; and (c) dialysis normalizes the glycemic response to glucagon, possibly accounting thereby for improved glucose tolerance despite persistent hyperglucagonemia. These findings thus provide evidence of decreased hormonal catabolism contributing to a hyperglucagonemic state, and of altered tissue sensitivity contributing to the pathophysiological action of this hormone.